Double brooding attempt by African Black Oystercatchers on Castle Rock, Knysna - du Toit, Johanna M (Biodiversity Observations, 2014)
Keeping the latest observations in mind (Koeberg, Soetwater and now Brenton-on-Sea), it may be possible that double brooding is more common then previously thought, as it can be easily overlooked on the higher density breeding sites. Future research may look at factors contributing to certain pairs double brooding within a single season, as well as the resultant effect on offspring numbers. Current oystercatcher monitors should therefore take extra care to record potential double broods and publish the results.